العلاقة التفاعلية بين مبادئ ممارسات علاقة المستثمرين ومستوى الإفصاح السردي بتقارير الإفصاح ربع السنوية وأثرها على سيولة الأسهم: دراسة تطبيقية على الشركات المقيدة بالبورصة المصرية - محمد، حسناء عطية حامد Mohammed, Hasna Attiah Hamed (جامعة طنطا - كلية التجارة - قسم المحاسبة, 2020)
This research aims to measure the relationship between the principles of investor relations practices and the level of narrative disclosure with quarterly disclosure reports prepared by the Investor Relations Department, in addition to measuring the impact of this interactive relationship on Stock Liquidity of companies listed on the Egyptian Stock Exchange, using a sample of 36 non-financial companies on the Egyptian Stock Exchange from various economic sectors during the period (2015; 2017), The results showed that: -there is a significant difference between the companies representing on the research sample in the level of the narrative disclosure in the quarterly disclosure reports,Where the index of the narrative disclosure ranged from (65%: 85%), which indicates the high level of narrative disclosure in the quarterly disclosure reports, also that there was a significant impact on the number of positions of the Investor Relations Officer at the level of narrative disclosure, which makes it more confident and credible in the information disclosed, in addition to that there was a significant positive impact of the interactive relationship between the principles of investor relations and the level of narrative disclosure quarterly disclosure reports on the Stock Liquidity.
يستهدف هذا البحث قياس العلاقة بين مبادئ ممارسات علاقات المستثمرين ومستوى الإفصاح السردي بتقارير الإفصاح ربع السنوية التي تعدها إدارة علاقات المستثمرين، بالإضافة إلى قياس تأثير هذه العلاقة التفاعلية (في حالة وجودها) على سيولة الأسهم للشركات المقيدة في البورصة المصرية، وقد تم ذلك بالتطبيق على عينة من ٣٦ شركة مساهمة غير مالية من الشركات المقيدة بالبورصة المصرية من مختلف القطاعات الاقتصادية خلال الفترة من (2015: 2017)، وأوضحت النتائج وجود اختلاف معنوي بين الشركات الممثلة لعينة البحث في مستوى الإفصاح السردي بتقارير الإفصاح ربع السنوية حيث تراوح مؤشر الإفصاح السردي من (65%: 85%) مما يشير إلى ارتفاع مستوى الإفصاح السردي في تقارير الإفصاح ربع السنوية، كما تبين وجود ارتباط إيجابي معنوي بين مبادئ علاقات المستثمرين ومستوى الإفصاح السردي بتقارير الإفصاح ربع السنوية، ووجود تأثير معنوي لتعدد مناصب مسئول علاقات المستثمرين على مستوى الإفصاح السردي والتي تجعله يحظى بمزيد من الثقة والمصداقية في المعلومات التي يفصح عنها، بالإضافة إلى أنه اتضح وجود تأثير إيجابي معنوي للعلاقة التفاعلية بين مبادئ علاقات المستثمرين ومستوى الإفصاح السردي بتقارير الإفصاح ربع السنوية على سيولة الأسهم.
Keywords: علاقات المستثمرين -- البورصة المصرية -- شركات الاستثمار -- الإفصاح السردي